Composite, sheet, electrochemical element, and electricity storage device

By attaching ionic liquid to the surface of metal oxide in electrochemical components, between the ester solvent and the metal oxide, the problem of degradation of conductivity caused by the decomposition of ester solvents is solved, and the composite and electrochemical components are realized Conductivity stability and working stability.

CN119301701APending Publication Date: 2025-01-10NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380043507.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-05-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, the conductivity of the composite is reduced when the ester solvent is decomposed, making it difficult to ensure the stability of the conductivity of the electrochemical components and the electrical storage devices.

Method used

The ionic liquid is attached to the surface of the metal oxide in the composite, and is between the ester solvents with electrolyte salts and the metal oxides. By controlling the proportion and structure of the ionic liquid, the decomposition of the ester solvents is reduced, thereby maintaining the Conductivity.

Benefits of technology

It effectively inhibits the decomposition of ester solvents, ensures the conductivity of composites, sheets, electrochemical components and electrical storage devices, and improves the working stability and life of electrochemical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301701A_ABST
    Figure CN119301701A_ABST
Patent Text Reader

Abstract

Provided are a composite, a sheet, an electrochemical element, and an electricity storage device with which conductivity can be ensured. The composite (10) contains an ester-based solvent (23) in which an electrolyte salt is dissolved and a metal oxide (19), and an ionic liquid (22) adheres to the surface of the metal oxide. The sheet (12) comprises a composite. The electrochemical element (11) contains the composite. An electricity storage device (11) is provided with a positive electrode layer (12), a negative electrode layer (16), and a separator (15) that separates the positive electrode layer from the negative electrode layer, and contains a composite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite, a sheet comprising the composite, an electrochemical element and an electricity storage device. Background Art

[0002] Patent Document 1 discloses a prior art related to a non-aqueous electrolyte (complex) comprising an organic solvent (ester solvent) composed of a chain carbonate or a cyclic carbonate in which a lithium salt (electrolyte salt) is dissolved, and an oxide solid electrolyte (metal oxide) having a garnet structure.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-45965 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the prior art, an ester solvent in contact with a metal oxide may decompose. When the ester solvent decomposes, the conductivity of the composite decreases.

[0008] The present invention has been made to solve this problem, and an object of the present invention is to provide a composite, a sheet, an electrochemical element, and a power storage device capable of ensuring electrical conductivity.

[0009] Methods used to solve problems

[0010] A first aspect for achieving the above object is a composite comprising an ester solvent in which an electrolyte salt is dissolved and a metal oxide, wherein an ionic liquid is attached to the surface of the metal oxide.

[0011] The second method is as follows: in the first method, when the calorific value (J / g) in the differential scanning calorimetry analysis caused by the solidification of an ionic liquid having the same molecular structure as the ionic liquid contained in the composite is set to Q1, and the calorific value (J / g) in the differential scanning calorimetry analysis caused by the solidification of an ionic liquid of a mixture in which an ionic liquid having the same molecular structure as the ionic liquid and a metal oxide contained in the composite and a metal oxide are mixed in the same proportion as that in the composite is set to Q2, the value of Q2 / Q1 is less than 0.5.

[0012] The third embodiment is as follows: In the first embodiment or the second embodiment, the surface area of ​​the metal oxide is S (m 2 ), the volume of the ionic liquid is set to V (m 3 ), V / S×10 9 The value of is greater than or equal to 1 nm and less than or equal to 40 nm.

[0013] The fourth embodiment is as follows: in the third embodiment, the ionic liquid contains fluorine atoms in its molecular structure, and the ionic liquid having the same molecular structure as the ionic liquid contained in the composite and the metal oxide are mixed in the same ratio as in the composite. The half width W1 of at least one of the signals of the fluorine atoms contained in the ionic liquid in the first mixture is measured by fluorine-19 nuclear magnetic resonance spectroscopy, and the half width W2 of at least one of the signals of the fluorine atoms contained in the ionic liquid in the first mixture is measured by fluorine-19 nuclear magnetic resonance spectroscopy using the ionic liquid having the same molecular structure as the ionic liquid contained in the composite and the metal oxide in the same ratio as in the composite. 9 The half width W2 of the signal of the fluorine atoms contained in the second mixture prepared so that the value of reaches 35 nm measured by fluorine-19 nuclear magnetic resonance spectroscopy is W1 / W2≥1.1.

[0014] A fifth aspect is a sheet comprising the composite according to any one of the first to fourth aspects.

[0015] A sixth aspect is an electrochemical device including the composite according to any one of the first to fourth aspects.

[0016] A seventh aspect is an electricity storage device including a positive electrode layer, a negative electrode layer, and a separator separating the positive electrode layer from the negative electrode layer, the device comprising the composite according to any one of the first to fourth aspects.

[0017] An eighth aspect is as follows: In the seventh aspect, at least one of the positive electrode layer, the negative electrode layer, and the separator includes a composite.

[0018] A ninth aspect is as follows: in the seventh aspect, at least one of the positive electrode layer and the negative electrode layer includes a current collecting layer, and has a protective layer in contact with at least one of the separator and the current collecting layer, and the protective layer includes a composite material.

[0019] Effects of the Invention

[0020] According to the composite of the present invention, the ionic liquid is interposed between the ester solvent in which the electrolyte salt is dissolved and the metal oxide, so the amount of the ester solvent in direct contact with the metal oxide can be reduced. The decomposition of the ester solvent is suppressed, so the conductivity of the composite, the sheet including the composite, the electrochemical element, and the storage device can be ensured. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a cross-sectional view of the electrochemical device including the composite in the first embodiment.

[0022] Figure 2 is a cross-sectional view of the composite.

[0023] Figure 3 This is a diagram schematically showing a garnet-type crystal structure.

[0024] Figure 4It is a cross-sectional view of the electrochemical device in the second embodiment.

[0025] Figure 5 It is a cross-sectional view of the electrochemical device in the third embodiment. DETAILED DESCRIPTION

[0026] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. Figure 1 1 is a schematic cross-sectional view of an electrochemical element 11 including a composite 10 in the first embodiment. The electrochemical element 11 in this embodiment is a lithium-ion solid-state battery (electricity storage device) in which the power generation element is composed of a solid. The power generation element is composed of a solid means that the skeleton of the power generation element is composed of a solid, including a method in which the skeleton is impregnated with a liquid.

[0027] The electrochemical element 11 includes a positive electrode layer 12, an electrolyte layer 15 and a negative electrode layer 16 in sequence. The positive electrode layer 12, the electrolyte layer 15 and the negative electrode layer 16 are all sheets. The positive electrode layer 12, the electrolyte layer 15 and the negative electrode layer 16 are accommodated in a casing (not shown). The electrolyte layer 15 includes a composite 10. The composite 10 includes a metal oxide 19. The electrolyte layer 15 in this embodiment is equivalent to a separator. The separator separates the positive electrode layer 12 from the negative electrode layer 16, so that they are electrically insulated from each other.

[0028] The positive electrode layer 12 is stacked with a collector layer 13 and a composite layer 14. The collector layer 13 is a conductive member. Examples of the material of the collector layer 13 include metals selected from Ni, Ti, Fe and Al, alloys containing two or more of these elements, stainless steel, and carbon materials.

[0029] The composite layer 14 includes the composite 10 and the active material 20. In order to reduce the resistance of the composite layer 14, a conductive additive may be included in the composite layer 14. Examples of the conductive additive include carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag.

[0030] Examples of the active material 20 include metal oxides containing transition metals, sulfur-based active materials, and organic active materials. Examples of metal oxides containing transition metals include metal oxides containing one or more elements selected from Mn, Co, Ni, Fe, Cr, and V, and Li. Examples of metal oxides containing transition metals include LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMn2O4, LiNiVO4, LiNi 0.5 Mn 1.5 O2、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiFePO4.

[0031] In order to suppress the reaction between the active material 20 and the metal oxide 19, a coating layer may be provided on the surface of the active material 20. Examples of the coating layer include Al2O3, ZrO2, LiNbO3, Li4Ti5O 12 , LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4 and Li2MoO4.

[0032] Examples of sulfur-based active materials include S, TiS2, NiS, FeS2, Li2S, MoS3, and sulfur-carbon composite materials. Examples of organic active materials include free radical compounds represented by 2,2,6,6-tetramethylpiperidinyloxy-4-yl methacrylate and polytetramethylpiperidinyloxyvinyl ether, quinone compounds, radialene compounds, tetracyanobenzoquinodimethane, and phenazine oxides.

[0033] The negative electrode layer 16 is stacked with a collector layer 17 and a composite layer 18. The collector layer 17 is a conductive member. Examples of the material of the collector layer 17 include metals selected from Ni, Ti, Fe, Cu and Si, alloys containing two or more of these elements, stainless steel, and carbon materials.

[0034] The composite layer 18 includes the composite 10 and the active material 21. In order to reduce the resistance of the composite layer 18, the composite layer 18 may include a conductive additive. Examples of the conductive additive include carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag. Examples of the active material 21 include Li, Li-Al alloy, Li4Ti5O 12 , graphite, In, Si, Si-Li alloy and SiO.

[0035] Figure 2 is a cross-sectional view of the composite 10 . Figure 2 A part of the cross section of the composite 10 is enlarged and schematically shown. The composite 10 includes a metal oxide 19, an ionic liquid 22, and an ester solvent 23 in which an electrolyte salt is dissolved. The ionic liquid 22 adheres to the surface of the metal oxide 19. The ionic liquid 22 is interposed between the metal oxide 19 and the ester solvent 23.

[0036] Metal oxide 19 is a component for forming composite 10, and is an oxide of a metal element. Metal oxide 19 is an alkaline oxide. Examples of metal elements constituting metal oxide 19 include: Group 1 elements such as Li, Na, and K; Group 2 elements such as Mg, Ca, and Sr; transition metals such as Sc, Y, Ti, Zr, V, Nb, Cr, Mo, Mn, Fe, Co, Ni, and Cu; lanthanides; actinides; semimetals such as Ga, Ge, In, Sb, and Bi. Al, Zn, Sn, and Pb (amphoteric elements) are not included in the metal elements. Metal oxide 19 may also include an amphoteric element as long as it contains one or more metal elements.

[0037] Examples of the metal oxide 19 include Li2O, MgO, Y2O3, TiO2, ZrO2, Nb2O5, Cr2O3, and NiO. Ion conductors composed of composite oxides containing Li, La, and Zr and having a garnet-type or garnet-like crystal structure are also included in the metal oxide 19. The metal oxide 19 can be selected from one or more of particles that do not have ionic conductivity and ion conductors.

[0038] Figure 3 It is a diagram schematically showing a garnet-type crystal structure. In the garnet-type crystal structure, the C site Sc is coordinated with the oxygen atom Oa in a dodecahedral manner, the A site Sa is coordinated with the oxygen atom Oa in an octahedral manner, and the B site Sb is coordinated with the oxygen atom Oa in a tetrahedral manner. In a conventional garnet-type crystal structure, Li may exist in a site that is octahedrally coordinated with the oxygen atom Oa and forms a void V. The void V is, for example, a site sandwiched by the B site Sb1 and the B site Sb2. The Li present in the void V is octahedrally coordinated with the oxygen atom Oa constituting an octahedron including the face Fb1 of the tetrahedron forming the B site Sb1 and the face Fb2 of the tetrahedron forming the B site Sb2. For example, Li7La3Zr2O having a garnet-type crystal structure 12 In the structure, La can occupy the C site Sc, Zr can occupy the A site Sa, and Li can occupy the B site Sb and the void V.

[0039] The ion conductor composed of a composite oxide having a garnet-type or garnet-like crystal structure has an X-ray diffraction pattern similar to that of CSD (Cambridge Structural Database) file No. 422259 (Li7La3Zr2O 12) has a similar XRD pattern. The ion conductor may have different types of constituent elements, Li concentration, etc. compared to No. 422259, so the diffraction angle and intensity ratio may be different. The representative crystal structure of ion conductors is cubic (space group Ia-3d (- represents an overline indicating a rotation-inversion operation), JCPDS: 84-1753). Among ion conductors, Li7La3Zr2O 12 A part of the constituent elements may be replaced by other elements, or a trace amount of other elements may be added without replacing the constituent elements. The other elements may be exemplified by at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb and lanthanoid elements (excluding La).

[0040] Ionic conductors include Li6La3Zr 1.5 W 0.5 O 12 , Li 6.15 Ln3Z 1.75 Ta 0.25 Al 0.2 O 12 , Li 6.15 Ln3Z 1.75 Ta 0.25 Ga 0.2 O 12 , Li 6.25 La3Zr2Ga 0.25 O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 6.5 Ln3Z 1.75 Te 0.25 O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 , Li 6.9 Ln3Z 1.675 Ta 0.289 Bi 0.036 O 12 , Li 6.46 Ga 0.23 Ln3Z 1.85 Y 0.15 O 12 , Li 6.8 La 2.95 Ca 0.05 Zr 1.75 Nb 0.25 O 12, Li 7.05 La 3.00 Zr 1.95 G 0.05 O 12 , Li 6.20 Ba 0.30 La 2.95 R 0.05 Zr2O 12 .

[0041] The ion conductor is particularly preferably: an ion conductor containing at least one of Mg and element A (A is at least one element selected from the group consisting of Ca, Sr and Ba) and the molar ratio of each element satisfies all of the following (1) to (3); or an ion conductor containing both Mg and element A and the molar ratio of each element satisfies all of the following (4) to (6). In order to improve the ionic conductivity of the metal oxide 19, element A is preferably Sr.

[0042] (1) 1.33 ≤ Li / (La+A) ≤ 3

[0043] (2) 0≤Mg / (La+A)≤0.5

[0044] (3)0≤A / (La+A)≤0.67

[0045] (4) 2.0≤Li / (La+A)≤2.5

[0046] (5) 0.01≤Mg / (La+A)≤0.14

[0047] (6) 0.04 ≤ A / (La+A) ≤ 0.17

[0048] As other ion conductors, crystalline or amorphous metal oxides such as perovskite type, NASICON type, and LISICON type can be cited. Perovskite type metal oxides include oxides containing at least Li, Ti, and La, such as La 2 / 3- X Li 3X TiO3. NASICON-type metal oxides include oxides containing at least Li, M (M is one or more elements selected from Ti, Zr and Ge) and P, such as Li(Al, Ti)2(PO4)3 and Li(Al, Ge)2(PO4)3. LISICON-type metal oxides include Li 14 Zn(GeO4)4.

[0049] The ionic liquid 22 is a compound composed of cations and anions and is liquid at room temperature and pressure. The ionic liquid 22 is preferably selected from ammonium, imidazole, Pyrrolidine and piperidine One or more species of the group consisting of are used as cationic species.

[0050] The ammonium cation is, for example, a compound represented by formula (1).

[0051]

[0052] In formula (1), R 1 -R 4 Each independently represents an alkyl group. The alkyl group may have a substituent. 1 -R 4 The number of carbon atoms in the alkyl group (including substituents) is preferably 1 to 5, more preferably 1 to 4. This is to ensure the ion conductivity of the electrolyte.

[0053] The substituent is not particularly limited and examples of the substituent include alkyl, cycloalkyl, aryl, hydroxy, carboxyl, nitro, trifluoromethyl, amide, carbamoyl, ester, carbonyloxy, cyano, halogen, alkoxy, aryloxy, and sulfonamide groups.

[0054] Imidazole The cation is, for example, a compound represented by formula (2).

[0055]

[0056] In formula (2), R 5 -R 9 Each independently represents a hydrogen group or an alkyl group. The alkyl group may have the same substituent as in formula (1). 5 -R 9 The number of carbon atoms in the alkyl group (including substituents) is preferably 1 to 10, more preferably 1 to 5, and even more preferably 1 to 4. This is to ensure the ion conductivity of the electrolyte.

[0057] Pyrrolidine The cation is, for example, a five-membered ring compound represented by formula (3).

[0058]

[0059] In formula (3), R 10 and R 11 Each independently represents an alkyl group. The alkyl group may have the same substituent as in formula (1). 10 and R 11 The number of carbon atoms in the alkyl group (including substituents) is preferably 1 to 5, more preferably 1 to 4. This is to ensure the ion conductivity of the electrolyte.

[0060] Piperidine The cation is, for example, a six-membered ring compound represented by formula (4).

[0061]

[0062] In formula (4), R 12 and R 13 Each independently represents an alkyl group. The alkyl group may have the same substituent as in formula (1). 12 and R 13 The number of carbon atoms in the alkyl group (including substituents) is preferably 1 to 5, more preferably 1 to 4. This is to ensure the ion conductivity of the electrolyte.

[0063] The anion component of the ionic liquid 22 is not particularly limited. Examples of the anion component include BF4 - 、N(SO2F)2 - Inorganic anions such as B(C6H5)4 - 、CH3SO3 - CF3SO3 - 、N(SO2CF3)2 - 、N(SO2C4F9)2 - Sometimes N(SO2F)2 - Abbreviated as [FSI] - : Bis(fluorosulfonyl)imide anion, N(SO2CF3)2 - Abbreviated as [TFSI] - : Bis(trifluoromethanesulfonyl)imide anion.

[0064] Examples of the ionic liquid 22 include N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide (DEME-FSI), N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide (DEME-TFSI), 1-ethyl-3-methylimidazole Bis(fluorosulfonyl)imide (EMI-FSI), 1-ethyl-3-methylimidazole Bis(trifluoromethanesulfonyl)imide (EMI-TFSI), N-butyl-N-methylpiperidine Bis(fluorosulfonyl)imide, N-methyl-N-propylpiperidine Bis(trifluoromethanesulfonyl)imide, N-methyl-N-propylpyrrolidine Bis(fluorosulfonyl)imide (P13-FSI), N-methyl-N-propylpyrrolidine Bis(trifluoromethanesulfonyl)imide (P13-TFSI). It may also be a mixture thereof.

[0065] The water content in the ionic liquid 22 is preferably 200 ppm or less. This is to prevent the potential window from being narrowed due to the water content in the ionic liquid 22. The halogen ions contained as impurities in the ionic liquid 22 are preferably 10 ppm or less. Other impurities contained in the ionic liquid 22 can be exemplified by alkali metal ions and alkaline earth metal ions. The sum of these impurities is preferably 10 ppm or less. This is to prevent the cycle characteristics of the electrochemical element 11 including the composite 10 from being reduced.

[0066] The composite 10 includes an ester solvent 23 in which an electrolyte salt is dissolved, that is, an electrolyte solution. The electrolyte salt is a compound used for the transfer of cations between the positive electrode layer 12 and the negative electrode layer 16. Examples of anions of the electrolyte salt include halogen ions (I - , Cl - Br - etc.), SCN - 、BF4 - 、BF3(CF3) - 、BF3(C2F5) - PF6 - 、ClO4 - 、SbF6 - 、N(SO2F)2 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、B(C6H5)4 - 、B(O2C2H4)2 - 、C(SO2F)3 - 、C(SO2CF3)3 - CF3COO - CF3SO2O - 、C6F5SO2O - 、B(O2C2O2)2 - ,RCOO - (R is an alkyl group having 1 to 4 carbon atoms, a phenyl group or a naphthyl group), etc. The electrolyte salt may be a mixture thereof.

[0067] The ionic liquid 22 may be a solvated ionic liquid. Examples of the solvated ionic liquid include ionic liquids obtained by dissolving a lithium salt such as lithium bis(fluorosulfonyl)imide in a sulfone-based solvent such as sulfolane or a sulfolane derivative, or a glycol dimethyl ether-based solvent such as tetraethylene glycol dimethyl ether.

[0068] One or more electrolyte salts may be dissolved in the ionic liquid 22. When an electrolyte salt is dissolved in the ionic liquid 22, for example, the salt concentration of the ionic liquid 22 is lower than the salt concentration of the ester solvent 23.

[0069] The anion of the electrolyte salt is preferably N(SO2F)2 having a sulfonyl group -S(=O)2- - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - Sulfonyl imide. This is because, for sulfonyl imide anions, even if the salt concentration becomes high, the effect of increased viscosity and decreased ionic conductivity of the ester solvent 23 is small, and by forming a coating (SEI) with high stability and low resistance, the reductive decomposition of the ester solvent 23 can be reduced and the reduction side potential window can be expanded. In the case where the cation is a lithium ion, the electrolyte salt is particularly preferably lithium bis(fluorosulfonyl)imide (LiFSI). This is because, for LiFSI, the effect of increased viscosity of the ester solvent 23 is small, and it is effective for the formation of a good passivation coating (SEI).

[0070] Examples of the ester solvent 23 include carbonates, aliphatic carboxylic acid esters, phosphates, sulfates, and γ-lactones. They may also be derivatives or mixtures thereof. The ester solvent 23 has low viscosity and an appropriate dielectric constant and potential window, and is therefore suitable as an organic solvent for dissolving an electrolyte salt.

[0071] Examples of carbonate esters include cyclic carbonates such as propylene carbonate, ethylene carbonate, butylene carbonate, vinylene carbonate, vinylethylene carbonate, and fluoroethylene carbonate, and chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of aliphatic carboxylic acid esters include methyl formate, methyl acetate, ethyl propionate, and dimethyl methylphosphonate. Examples of phosphate esters include trimethyl phosphate and triethyl phosphate. Examples of sulfate esters include sultones. Examples of γ-lactones include γ-butyrolactone.

[0072] The concentration of the electrolyte salt in the ester solvent 23 is 0.2 mol / dm 3 More than, preferably 0.5 mol / dm 3 As the salt concentration increases, the number of solvent molecules coordinated to the carrier ions increases, and the number of uncoordinated solvent molecules decreases, so that the interface resistance of the metal oxide 19 can be reduced.

[0073] The salt concentration of the ester solvent 23 is preferably 4.0 mol / dm 3 This is because the salt concentration of the ester solvent 23 is greater than 4.0 mol / dm 3 When the viscosity of the ester solvent 23 increases, the ionic conductivity tends to decrease significantly.

[0074] The electrolyte contained in the composite 10 may contain other organic solvents in addition to the ester solvent 23. Other organic solvents, for example, help reduce the viscosity of the ester solvent 23 and increase ion conductivity. Examples of other organic solvents include acetonitrile, isobutyl methyl ketone, nitromethane, methyl ethyl ketone, and tetramethylsilane. One or more other organic solvents that are not likely to affect the coordination state of carrier ions and solvent molecules can be appropriately selected.

[0075] The salt concentration of the ester solvent 23 included in the composite 10 is determined, for example, as follows. Here, the composite 10 constituting the electrolyte layer 15 is described, but the salt concentration of the composite 10 constituting the composite layers 14 and 18 can be determined in the same manner.

[0076] First, the electrolyte layer 15 is crushed and immersed in a solvent, and the electrolyte solution contained in the electrolyte layer 15 is dissolved in the solvent, and then separated into a solid component and a liquid component by a centrifugal separator. The Li content of the separated liquid component is determined by high-frequency inductively coupled plasma analysis (ICP).

[0077] In addition, the type of organic solvent contained in the electrolyte layer 15 is determined by, for example, gas chromatography-mass spectrometry (GC-MS). The organic solvent of the determined type (hereinafter referred to as "standard substance") and the electrolyte layer 15 are analyzed by thermogravimetric differential thermal analysis (TG-DTA), and the analysis results of the standard substance are compared with the analysis results of the electrolyte layer 15 to determine the content of the ester solvent 23 contained in the electrolyte layer 15. Based on the content of Li in the liquid component and the content of the ester solvent 23 in the electrolyte layer 15, the molar concentration (mol / dm 3 ).

[0078] In the composite 10, the ionic liquid 22 is interposed between the ester solvent 23 in which the electrolyte salt is dissolved and the alkaline metal oxide 19. The ionic liquid 22 may be attached to the entire metal oxide 19 or to a portion of the metal oxide 19. The ionic liquid 22 may be attached to the entire surface of the metal oxide 19 or to a portion of the surface of the metal oxide 19. When the ionic liquid 22 is attached to the surface of the metal oxide 19, the amount of the ester solvent 23 in direct contact with the metal oxide 19 can be reduced. Since the decomposition of the ester solvent 23 can be suppressed, the conductivity of the composite 10 can be ensured. In addition, since the decomposition of the ester solvent 23 can be suppressed, various ester solvents 23 can be appropriately selected.

[0079] The surface area of ​​the metal oxide 19 contained in the composite 10 is denoted as S (m 2 ), the volume of the ionic liquid 22 contained in the composite 10 is set to V (m 3), V / S×10 9 The value of (hereinafter referred to as "T") may be greater than 1 nm and less than 40 nm. T refers to the average value (nm) of the thickness of the ionic liquid 22 attached to the surface of the metal oxide 19 contained in the composite 10. When T is greater than 1 nm and less than 40 nm, the amount of the ionic liquid 22 used can be reduced, and the amount of the ester solvent 23 affected by the metal oxide 19 can be further reduced. The decomposition of the ester solvent 23 is further reduced, so that the conductivity of the composite 10 can be ensured.

[0080] The surface area of ​​the metal oxide 19 contained in the composite 10 can be determined based on a method utilizing gas adsorption (BET method) or analysis of an image obtained by a scanning electron microscope (SEM) of a cross section of the composite 10. With regard to the surface area obtained by gas adsorption, after repeatedly washing the composite 10 taken out of the electrochemical element 11 with an organic solvent and separating the metal oxide 19 by centrifugal separation, the specific surface area of ​​the metal oxide 19 is measured with reference to JIS Z8830:2013, and the surface area is obtained by multiplying the mass of the metal oxide 19 by the specific surface area.

[0081] Before measuring the specific surface area, degassing treatment is performed in an inert gas (e.g., He) atmosphere (e.g., at a temperature of 200°C for 60 minutes) to remove substances physically adsorbed on the surface of the metal oxide 19. For example, the adsorbed gas used in the measurement of the specific surface area is a mixed gas (He:N2=7:3), and the amount of adsorbed gas is measured by a flow method. The parameters are calculated by a single point method. Regarding the surface area of ​​the metal oxide 19 obtained by image analysis, the equivalent circle diameter of the metal oxide 19 appearing in the SEM image of the cross section of the composite 10 is obtained by image analysis, and the surface area of ​​the metal oxide 19 is obtained by the sum of the surface areas of spheres with the equivalent circle diameter as the diameter.

[0082] The ratio (volume %) of the metal oxide 19 and the ionic liquid 22 contained in the composite 10 can be obtained by SEM images or chemical analysis of the cross section of the composite 10. In order to obtain the volume of the ionic liquid 22 based on the SEM image, first, the composite 10 is frozen using liquid nitrogen or the like, or the composite 10 is embedded in a tetrafunctional epoxy resin or the like, and after the composite 10 is fixed, a cross section is obtained by grinding, focused ion beam (FIB) irradiation, or ion milling.

[0083] Next, using a SEM equipped with an energy dispersive X-ray spectrometer (EDS), a 5000-fold field of view randomly selected from the cross section is used as an object to determine the distribution of elements constituting the metal oxide 19 and the ionic liquid 22 or to perform image analysis on the contrast of the reflected electron image. In this way, the area occupied by the metal oxide 19 and the ionic liquid 22 in the cross section of the composite 10 is measured. The area of ​​the metal oxide 19 and the ionic liquid 22 in the cross section is converted to obtain the ratio (volume %) of the metal oxide 19 and the ionic liquid 22.

[0084] The volume of the ionic liquid 22 obtained by chemical analysis can be obtained by measuring the concentration of the ionic liquid 22 after determining the type of the ionic liquid 22. The type of the ionic liquid 22 can be determined by GC-MS, Fourier transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance spectroscopy ( 1 H-NMR), carbon 13 nuclear magnetic resonance spectroscopy ( 13 C-NMR) etc. The concentration of the ionic liquid 22 can be determined by 1 It can be determined by H-NMR etc.

[0085] The median diameter of the equivalent circle diameter of the metal oxide 19 appearing in the cross section of the composite 10 is preferably 0.5-10 μm, more preferably 0.5-6 μm. This is to make the surface area of ​​the metal oxide 19 of an appropriate size, thereby ensuring the amount of ion movement between the electrolyte present on the surface of the metal oxide 19 and the metal oxide 19.

[0086] In order to obtain the median diameter of the metal oxide 19, first, the SEM image of the metal oxide 19 appearing in the cross section of the composite 10 is analyzed, and the equivalent circle diameter is calculated from the area of ​​each particle of the metal oxide 19 to obtain the volume-based particle size distribution. The median diameter is the equivalent circle diameter at which the integral value of the frequency in the particle size distribution is 50%. In order to ensure accuracy, the image for obtaining the particle size distribution is set to 400 μm in the cross section. 2 The area above.

[0087] The composite 10 preferably has most of the ionic liquid 22 adsorbed on the metal oxide 19. The thermal properties of the ionic liquid 22 adsorbed on the metal oxide 19 change compared to the free ionic liquid not adsorbed on the metal oxide 19. Therefore, the calorific value Q2 (J / g) in the differential scanning calorimetry (DSC) caused by the solidification of the ionic liquid of the mixture obtained by mixing the ionic liquid 22 and the metal oxide 19 having the same molecular structure as the ionic liquid 22 and the metal oxide 19 contained in the composite 10 in the same ratio as that in the composite 10 is smaller than the calorific value Q1 (J / g) in the DSC caused by the solidification of the ionic liquid having the same molecular structure as the ionic liquid 22 contained in the composite 10.

[0088] The metal oxide 19 and the ionic liquid 22 may be mixed to satisfy the relationship Q2 / Q1<0.5. Satisfying the relationship Q2 / Q1<0.5 means that most of the ionic liquid 22 contained in the composite 10 is adsorbed on the metal oxide 19, that is, most of the ionic liquid 22 is between the metal oxide 19 and the ester solvent 23.

[0089] The molecular structure of ionic liquid 22 can be determined by GC-MS, FT-IR, 1 H-NMR, 13 The ionic liquids 22 with the same molecular structure include ionic liquids with the same molecular skeleton, counter ion, alkyl chain length, etc. but different only in stereo conformation. The elemental analysis of the metal oxide 19 can be performed using, for example, fluorescent X-ray analysis (XRF). The structure of the metal oxide 19 can be determined by X-ray diffraction.

[0090] The ratio of the ionic liquid 22 to the metal oxide 19 in the composite 10 can be determined by measuring the concentration of the ionic liquid 22 and the mass of the metal oxide 19. The concentration of the ionic liquid 22 can be determined by 1 H-NMR, etc. The mass of the metal oxide 19 may be measured by repeatedly washing the composite 10 taken out from the electrochemical element 11 with an organic solvent and separating the metal oxide 19 by centrifugal separation, and then weighing the separated metal oxide 19.

[0091] The calorific value Q1 in DSC caused by the solidification of the ionic liquid can be obtained by referring to literature values ​​related to ionic liquids with a certain molecular structure. Alternatively, Q1 can be obtained by DSC measurement of a commercially available ionic liquid with a certain molecular structure.

[0092] The mixture for obtaining the calorific value Q2 is obtained by weighing an ionic liquid and a metal oxide having the same molecular structure as the ionic liquid 22 and the metal oxide 19 contained in the composite 10 in a ratio equal to that in the composite 10, for example, putting the metal oxide and the ionic liquid in a mortar and mixing them with a pestle. By measuring the mixture by DSC, Q2 caused by the solidification of the ionic liquid contained in the mixture can be obtained.

[0093] In the case where the measurement conditions of Q1 are recorded in the literature recording the value of Q1, the measurement conditions of Q2 are made the same as the conditions of Q1 recorded in the literature. In the case where the measurement conditions of Q1 are not recorded in the literature, Q1 and Q2 are measured under the same appropriate conditions. It is preferred to cool the sample at a scanning speed slower than the time of the phase change (phase change, structural relaxation) of the ionic liquid, and measure the calorific value Q1 and Q2 caused by the solidification occurring in the process. In the case where the sample becomes a supercooled state during the cooling process and no solidification occurs, the supercooled sample is heated at the same speed as the cooling scanning speed, and the calorific value caused by the crystallization (solidification) occurring during the heating process is taken as Q1 and Q2.

[0094] In the case where the ionic liquid 22 included in the composite 10 contains fluorine atoms in its molecular structure, the fluorine atoms contained in the ionic liquid (I) in the first mixture prepared by mixing the ionic liquid (I) having the same molecular structure as the ionic liquid 22 and the metal oxide (O) having the same structure as the metal oxide 19 in the same ratio as in the composite 10 are determined by fluorine-19 nuclear magnetic resonance spectroscopy ( 19 The half width W1 of at least one of the signals measured by F-NMR, and the V / S×10 9 The fluorine atoms contained in the ionic liquid (I) in the second mixture prepared in such a way that the value of 35 nm is reached are 19 The half width W2 of the signal measured by F-NMR can be set to W1 / W2≥1.1.

[0095] Regarding the ionic liquid 22 contained in the composite 10, it is presumed that the anions of the ionic liquid 22 are adsorbed on the metal oxide 19. The molecules of the ionic liquid 22 whose anions are adsorbed on the metal oxide 19 have lower molecular mobility than the free ionic liquid that is not adsorbed on the metal oxide 19. 19 The relaxation time from the excited state when the radiation of the radio wave pulse is stopped in F-NMR becomes shorter. The half width of the signal is proportional to the inverse of the relaxation time (T2), so the half width of the signal of the ionic liquid 22 adsorbed on the metal oxide 19 is increased compared with the half width of the free ionic liquid not adsorbed on the metal oxide 19.

[0096] The half width W1 of the signal from the ionic liquid (I) adsorbed on the metal oxide (O) in the first mixture is relative to the value of V / S×10 9The half width W2 of the signal derived from the ionic liquid in the second mixture of ionic liquid (I) and metal oxide (O) prepared in a manner so that the value reaches 35 nm is more than 1.1 times, indicating that most of the ionic liquid 22 contained in the composite 10 is adsorbed on the metal oxide 19, that is, most of the ionic liquid 22 is between the metal oxide 19 and the ester solvent 23.

[0097] In the composite 10, the ratio of the volume of the metal oxide 19 to the total volume of the metal oxide 19 and the electrolyte is 52% or more and less than 100%, preferably 61% or more and less than 100%. The combination of the metal oxide 19 and the electrolyte can significantly reduce the interface resistance of the metal oxide 19, so that the ion migration number of the composite 10 can be greater than the ion migration number of the ordinary electrolyte. As a result, the operating stability of the electrochemical element 11 equipped with the composite 10 is increased.

[0098] The composite 10 may include a binder for bonding the metal oxide 19. Examples of the binder include fluorinated resins, polyolefins, polyimides, polyvinyl pyrrolidone, polyvinyl alcohol, cellulose ethers, and rubber polymers such as styrene butadiene rubber. Examples of the fluorinated resin include vinylidene fluoride polymers, polytrifluorochloroethylene, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, and ethylene-chlorotrifluoroethylene copolymers.

[0099] Examples of vinylidene fluoride polymers include homopolymers of vinylidene fluoride and copolymers of vinylidene fluoride and copolymerizable monomers. Copolymerizable monomers include halogen-containing monomers (excluding vinylidene fluoride) and non-halogen copolymerizable monomers. Examples of halogen-containing monomers include: chlorine-containing monomers such as vinyl chloride; fluorine-containing monomers such as trifluoroethylene, tetrafluoroethylene, trifluorochloroethylene, hexafluoropropylene, and perfluoroalkyl vinyl ether. Examples of non-halogen copolymerizable monomers include: olefins such as ethylene and propylene; acrylic acid monomers such as acrylic acid, methacrylic acid, and their esters or salts; vinyl monomers such as acrylonitrile, vinyl acetate, and styrene. One or more of the copolymerizable monomers are polymerized with vinylidene fluoride to form a copolymer.

[0100] The ionic conductivity of the composite 10 is determined by the types of the metal oxide 19, the electrolyte salt and the electrolyte solution, the salt concentration, etc. The ionic conductivity of the composite 10 at 25° C. is preferably 4.0×10 -5 S / cm or more. This is to ensure the output density of the electrochemical device 11 including the composite 10.

[0101] The composite 10 contains anions from the electrolyte, so the ion conductivity of the composite 10 can be calculated by multiplying the total ion conductivity calculated by the AC impedance method of a symmetrical battery obtained by bonding current collectors to both surfaces of the composite 10 formed into a sheet by the transference number. The transference number is obtained by the AC impedance method and the steady-state DC method.

[0102] The electrochemical element 11 can be manufactured, for example, as follows. The metal oxide 19 compounded with the ionic liquid 22 is mixed with an ester solvent 23 in which an electrolyte salt is dissolved, and a solution obtained by dissolving a binder in the solvent is mixed therein to prepare a slurry. After tape forming, it is dried to obtain a green sheet (electrolyte sheet) for the electrolyte layer 15.

[0103] The metal oxide 19 compounded with the ionic liquid 22 is mixed with the ester solvent 23 in which the electrolyte salt is dissolved, and then the active material 20 is mixed therein, and then the solution obtained by dissolving the binder in the solvent is mixed to prepare a slurry. After the strip is formed on the collector layer 13, it is dried to obtain a green sheet (positive electrode sheet) for the positive electrode layer 12.

[0104] The metal oxide 19 compounded with the ionic liquid 22 is mixed with the ester solvent 23 in which the electrolyte salt is dissolved, and then the active material 21 is mixed therein, and then the solution obtained by dissolving the binder in the solvent is mixed to prepare a slurry. After the strip is formed on the collector layer 17, it is dried to obtain a raw sheet (negative electrode sheet) for the negative electrode layer 16.

[0105] After the electrolyte sheet, the positive electrode sheet and the negative electrode sheet are cut into predetermined shapes, they are stacked in the order of the positive electrode sheet, the electrolyte sheet and the negative electrode sheet, and are crimped to form an integral body. The terminals (not shown) are connected to the collector layers 13 and 17 respectively and sealed in a housing (not shown), thereby obtaining an electrochemical element 11 including a positive electrode layer 12, an electrolyte layer 15 and a negative electrode layer 16.

[0106] Reference Figure 4 The second embodiment is described. In the first embodiment, the case where the composite 10 is used in a secondary battery in which the power generation element is composed of a solid is described. In the second embodiment, the case where the composite 10 is used in a liquid lithium ion battery in which an organic solvent is used as an electrolyte is described. In the second embodiment, the same parts as those described in the first embodiment are denoted by the same reference numerals, and the following description is omitted. Figure 4 It is a cross-sectional view of an electrochemical element 24 (electricity storage device) in the second embodiment.

[0107] The electrochemical element 24 includes a positive electrode layer 12, a separator 25, and a negative electrode layer 16 in sequence. They are housed in a housing (not shown). The separator 25 is durable to the active materials 20, 21, and the electrolyte contained in the positive electrode layer 12 and the negative electrode layer 16, and is composed of a porous body through which lithium ions pass but is not conductive. The separator 25 can be exemplified by a non-woven fabric or a porous film composed of cellulose, polypropylene, polyethylene, etc. The electrolyte is the same as the electrolyte described in the first embodiment, so the description is omitted.

[0108] Since the electrochemical device 24 of the second embodiment includes the composite material 10 in the positive electrode layer 12 and the negative electrode layer 16 , the conductivity of the positive electrode layer 12 and the negative electrode layer 16 can be ensured similarly to the electrochemical device 11 of the first embodiment.

[0109] Reference Figure 5 The third embodiment is described. In the first and second embodiments, the case where the composite material 10 is included in the positive electrode layer 12, the electrolyte layer 15, and the negative electrode layer 16 is described. In the third embodiment, the case where the composite material 10 is included in the protective layers 29 and 32 is described. In the third embodiment, the same reference numerals are given to the same parts as those described in the first and second embodiments, and the following description is omitted. Figure 5 It is a cross-sectional view of an electrochemical element 26 (electricity storage device) in the third embodiment.

[0110] The electrochemical element 26 includes a positive electrode layer 27, a separator 25, and a negative electrode layer 30 in this order. These are housed in a case (not shown). The electrochemical element 26 is a liquid lithium ion battery using an organic solvent as an electrolyte.

[0111] The positive electrode layer 27 is stacked with the current collecting layer 13 and the active material layer 28. The active material layer 28 contains the active material 20. In order to reduce the resistance of the active material layer 28, the active material layer 28 may contain a conductive additive such as carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag.

[0112] A protective layer 29 is disposed between the separator 25 and the negative electrode layer 30 . The protective layer 29 includes the composite 10 .

[0113] In the negative electrode layer 30, an active material layer 31, a protective layer 32 and a current collecting layer 17 are stacked in this order. The active material layer 31 is composed of, for example, Li, Li-Al alloy, Li-Sn alloy, Li-Si alloy, Li-Mg alloy, Li-Si alloy or Si-Li alloy. The protective layer 32 contains the composite 10. The protective layers 29 and 32 can be configured by stacking sheets, coating on the separator 25 and the current collecting layer 17, etc.

[0114] The metal oxide 19 having a garnet-type crystal structure containing Li, La, Zr, and O is resistant to reduction of the metal lithium of the active material layer 31, thereby increasing the operating stability of the electrochemical element 26. The protective layer 29 between the active material layer 31 and the separator 25 suppresses short circuits caused by dendrite growth of the metal lithium. The protective layer 32 between the active material layer 31 and the collector layer 17 suppresses deterioration of the collector layer 17.

[0115] Example

[0116] The present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0117] (Preparation of Metal Oxides)

[0118] To become Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 Li2CO3, MgO, La(OH)3, SrCO3, and ZrO2 were weighed in a manner. Considering the volatilization of Li during calcination, Li2CO3 was set to an excess of about 15 mol% in terms of element conversion. The weighed raw materials and ethanol were put into a nylon can together with zirconium oxide balls, and crushed and mixed for 15 hours using a ball mill. After drying the slurry taken out of the can, pre-calculate it on a plate made of MgO (at 900°C for 1 hour). The pre-calcined powder and ethanol were put into a nylon can and crushed and mixed for 15 hours using a ball mill.

[0119] The slurry was dried and placed in a 12 mm diameter mold to obtain a molded body with a thickness of about 1.5 mm. The molded body was further subjected to a 1.5 t / cm2 cold isostatic press (CIP). 2 The molded body was covered with pre-fired powder of the same composition as the molded body and sintered in a reducing atmosphere (1100°C for 4 hours) to obtain a sintered body of the metal oxide. The lithium ion conductivity of the sintered body obtained by the AC impedance method was 1.0×10 -3 The lithium ion conductivity was measured under the following conditions: temperature 25° C., voltage 10 mV, and frequency 7 MHz to 100 mHz.

[0120] The sintered body was pulverized in an Ar atmosphere using a mortar to obtain a powdery metal oxide (hereinafter referred to as "LLZ"). The median diameter of the particle size distribution of LLZ measured by a laser diffraction / scattering method was about 3 μm.

[0121] (Preparation of Electrolyte)

[0122] The electrolyte salt LiN(SO2F)2(LiFSI) was dissolved in ethyl methyl carbonate to obtain a salt concentration of 2 mol / dm 3 of electrolyte.

[0123] (Example 1)

[0124] LLZ was mixed with the ionic liquid N-methyl-N-propylpyrrolidine Bis(fluorosulfonyl)imide (P13-FSI) was put into a mortar in a ratio of 86:4 (mass ratio), and compounded using a pestle to obtain a composite powder. The composite powder and the electrolyte were put into a mortar in a ratio of 90:10 (mass ratio), and compounded using a pestle to obtain the composite of Example 1.

[0125] (Example 2)

[0126] P13-FSI and the electrolyte were mixed in a ratio of 4:10 (mass ratio) to obtain a mixed solution. LLZ and the mixed solution were put into a mortar in a ratio of 86:14 (mass ratio) and compounded using a pestle to obtain the composite of Example 2.

[0127] (Example 3)

[0128] LLZ and P13-FSI were put into a mortar in a ratio of 80:17 (mass ratio), and compounded using a pestle to obtain a composite powder. The composite powder and the electrolyte were put into a mortar in a ratio of 97:3 (mass ratio), and compounded using a pestle to obtain the composite of Example 3.

[0129] (Example 4)

[0130] LiFSI was dissolved in P13-FSI to obtain a salt concentration of 3 mol / dm 3 LLZ and the mixed solution were placed in a mortar in a ratio of 80:17 (mass ratio), and compounded using a pestle to obtain a composite powder. The composite powder and the electrolyte were placed in a mortar in a ratio of 97:3 (mass ratio), and compounded using a pestle to obtain the composite of Example 4.

[0131] (Example 5)

[0132] Combining LLZ with LiNi 0.8 Co 0.15 Al 0.05O2 (hereinafter referred to as "NCA") was placed in a mortar in a ratio of 2.86:85.87 (mass ratio), and compounded using a pestle to obtain a mixed powder. The mixed powder and P13-FSI were placed in a mortar in a ratio of 88.73:1.27 (mass ratio), and compounded using a pestle to obtain a composite powder. The composite powder and the electrolyte were placed in a mortar in a ratio of 90:10 (mass ratio), and compounded using a pestle to obtain the composite of Example 5.

[0133] (Example 6)

[0134] LLZ and Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 (hereinafter referred to as "NMC") was placed in a mortar in a ratio of 2.95:86.54 (mass ratio), and compounded using a pestle to obtain a mixed powder. The mixed powder and P13-FSI were placed in a mortar in a ratio of 89.49:0.51 (mass ratio), and compounded using a pestle to obtain a composite powder. The composite powder and the electrolyte were placed in a mortar in a ratio of 90:10 (mass ratio), and compounded using a pestle to obtain the composite of Example 6.

[0135] (Comparative Example)

[0136] LLZ and the electrolyte were put into a mortar at a ratio of 85:15 (mass ratio), and compounded using a pestle to obtain a composite of a comparative example.

[0137] (V / S calculation)

[0138] The surface area of ​​LLZ contained in the composites of Examples 1 to 6 and Comparative Example is denoted as S (m 2 ), the volume of the ionic liquid contained in the complex is set to V (m 3 ), calculate V / S×10 9 The value (nm). It should be noted that the specific surface area of ​​LLZ was measured by the BET flow single point method (He: N2 = 7: 3) using a fully automatic specific surface area measuring device (HM-1208), and then the mass of LLZ contained in the composite was multiplied by the specific surface area to obtain the surface area of ​​LLZ. The sample for measuring the specific surface area was degassed at 200°C for 60 minutes in an inert atmosphere before the measurement.

[0139] (Calculation of Q2 / Q1)

[0140] The composites in Examples 1-6 were placed in aluminum pans, cooled at a rate of 5°C / min from 25°C in an Ar atmosphere, and differential scanning calorimetry analysis of the composites was performed to measure the calorific value Q2 (J / g) caused by the solidification of P13-FSI contained in the composites. Similarly, P13-FSI was placed in an aluminum pan, cooled at a rate of 5°C / min from 25°C in an Ar atmosphere, and differential scanning calorimetry analysis of P13-FSI was performed to measure the calorific value Q1 (J / g) caused by the solidification of P13-FSI, and Q2 / Q1 was calculated. The composite of the comparative example did not contain P13-FSI, so differential scanning calorimetry analysis was not performed.

[0141] (Measurement of resistance)

[0142] In an Ar atmosphere, the composites of Examples 1-6 and Comparative Examples were placed in a cylindrical insulating member with an inner diameter of 10 mm, and molded bodies of Examples 1-6 and Comparative Examples were obtained by uniaxial pressing at 500 MPa. The resistance of the molded bodies at 10 kHz at 25° C. was measured by an AC impedance method.

[0143] ( 19 Determination of half width of F-NMR signal)

[0144] In the same manner as in Example 1, LLZ and P13-FSI were placed in a mortar in a ratio of 86:4 (mass ratio) and compounded using a pestle to obtain a first mixture. 9 LLZ and P13-FSI were weighed and put into a mortar so that the value of 35 nm could reach 35 nm, and compounded using a pestle to obtain a second mixture.

[0145] The first mixture and the second mixture were added to the sample tube made of zirconium oxide, and the solid-state NMR device was used to measure the 19 F-NMR measurement. The measurement conditions were set to Larmor frequency: 564.73 MHz, magic angle rotation speed: 20 kHz, and magnetic field strength: 14.1 T. Signals representing fluorosulfonyl imide anions were observed around 53 ppm. The value obtained by dividing the half width W1 of the signal of the first mixture by the half width W2 of the signal of the second mixture (W1 / W2) was 1.1.

[0146] (result)

[0147] V / S (nm), Q2 / Q1, and resistance (Ω) are recorded in Table 1.

[0148]

[0149] The resistance of the composite in Example 1-4 is about 1 / 4 or less than that of the composite in the comparative example. It can be inferred that the composite in Example 1-4 has P13-FSI attached to the surface of LLZ, and P13-FSI is between LLZ and ethyl methyl carbonate. Therefore, compared with the composite in the comparative example, the decomposition of ethyl methyl carbonate is reduced and the resistance is reduced. It can be inferred that since NCA and NMC are conductive, the resistance of the composite in Examples 5 and 6 cannot be measured. However, since P13-FSI is attached to the surface of LLZ, the decomposition of ethyl methyl carbonate is reduced, similar to the composite in Example 1-4.

[0150] Liquid seepage occurred in the composites of Examples 3 and 4 when the molded bodies were made. Therefore, it can be said that the value of V / S is preferably less than 40 nm, and the value of Q2 / Q1 is preferably less than 0.5. It should be noted that the composite in Example 4 did not observe heat generation caused by solidification of the mixed solution in which LiFSI was dissolved in P13-FSI, so the value of Q2 / Q1 was 0.

[0151] V / S of the first mixture × 10 9 The value of V / S×10 is 8nm. 9 The smaller the value of , the higher the ratio of the ionic liquid adsorbed on the LLZ in the total ionic liquid present in the mixture. Therefore, the ratio of the ionic liquid adsorbed on the surface of the LLZ is higher in the second mixture than in the complexes in Examples 3 and 4, and the ratio of the ionic liquid adsorbed on the surface of the LLZ is higher in the first mixture than in the second mixture.

[0152] It can be inferred that: 19 In the composition with a large half width of the F-NMR signal, the molecular mobility of P13-FSI on the surface of LLZ is reduced, and the ratio of anions adsorbed on LLZ is high. It can be considered that: in terms of charge balance, it is shown that not only anions but also the ionic liquid containing cations itself is adsorbed on LLZ. Therefore, it can be considered that: the ratio of ionic liquid adsorbed on the surface of LLZ in the first mixture is higher than that in the second mixture, and the use of a small amount of ionic liquid can more effectively suppress the decomposition caused by the reaction of LLZ and the ester solvent. It should be noted that considering the V / S×10 of the second mixture compared with the composites of Examples 3 and 4 9 When the value of is small, it can be inferred that the second mixture also has an effect of inhibiting the decomposition of the ester solvent equal to or greater than that of Examples 3 and 4.

[0153] As mentioned above, although this invention was demonstrated based on embodiment, this invention is not limited to the said embodiment at all, It can be easily estimated that various improvements and modifications are possible within the range which does not deviate from the summary of this invention.

[0154] In the embodiment, as the electrochemical element 11, an electrochemical element having a positive electrode layer 12 having a composite layer 14 disposed on one side of a collector layer 13 and a negative electrode layer 16 having a composite layer 18 disposed on one side of a collector layer 17 is described, but it is not necessarily limited to this. For example, in an electric storage device having an electrode layer (so-called bipolar electrode) having composite layers 14 and 18 disposed on both sides of a collector layer 13, each element in the embodiment can of course be applied. If the bipolar electrode and the electrolyte layer 15 are alternately stacked and housed in a housing (not shown), a so-called bipolar structure electric storage device can be obtained.

[0155] In the first embodiment, the composite layers 14 and 18 and the electrolyte layer 15 both include the composite 10 , but the present invention is not necessarily limited thereto. In the electrochemical element 11 , at least one of the composite layers 14 and 18 and the electrolyte layer 15 may include the composite 10 .

[0156] In the second embodiment, the case where both the composite layers 14 and 18 include the composite material 10 is described, but the present invention is not necessarily limited to this. In the electrochemical element 24 , at least one of the composite layers 14 and 18 may include the composite material 10 .

[0157] In the third embodiment, the protective layer 29 is provided between the active material layer 31 and the separator 25 and the protective layer 32 is provided between the current collecting layer 17 and the active material layer 31 , but the present invention is not necessarily limited thereto. Of course, either the protective layer 29 or 32 may be omitted.

[0158] In the embodiment, the composite 10 is described by taking the electrochemical elements 11, 24, and 26 composed of lithium ion batteries as an example, but is not necessarily limited thereto. Other electrochemical elements including the composite 10 include lithium ion capacitors, lithium sulfur batteries, lithium oxygen batteries, lithium air batteries, and sodium ion batteries.

[0159] Explanation of symbols

[0160] 10 Complex

[0161] 11, 24, 26 Electrochemical components (electricity storage devices)

[0162] 12 positive electrode layer (sheet)

[0163] 15. Electrolyte layer (sheet, diaphragm)

[0164] 16 negative electrode layer (sheet)

[0165] 17 Collector layer

[0166] 19 Metal oxides

[0167] 22 Ionic Liquids

[0168] 23 Ester solvents

[0169] 25 Diaphragm

[0170] 27 Positive electrode layer

[0171] 29, 32 protective layer

[0172] 30 Negative electrode layer

Claims

1. A composite comprising an ester solvent in which an electrolyte salt is dissolved and a metal oxide, wherein: An ionic liquid is attached to the surface of the metal oxide.

2. The composite according to claim 1, wherein When the calorific value (J / g) in differential scanning calorimetry caused by solidification of an ionic liquid having the same molecular structure as the ionic liquid contained in the composite is set to Q1, and the calorific value (J / g) in differential scanning calorimetry caused by solidification of a mixture of an ionic liquid having the same molecular structure as the ionic liquid and the metal oxide contained in the composite and a metal oxide mixed in the same proportion as that in the composite is set to Q2, the value of Q2 / Q1 is less than 0.

5.

3. The composite according to claim 1 or 2, wherein: The surface area of ​​the metal oxide is denoted as S (m 2 ), the volume of the ionic liquid is set to V (m 3 ), V / S×10 9 The value of is greater than or equal to 1 nm and less than or equal to 40 nm.

4. The composite according to claim 3, wherein The ionic liquid contains fluorine atoms in its molecular structure. The half width W1 of at least one signal of the signals of the fluorine atoms contained in the ionic liquid measured by fluorine-19 nuclear magnetic resonance spectroscopy of the first mixture in which the ionic liquid having the same molecular structure as the ionic liquid contained in the composite and the metal oxide are mixed in the same ratio as in the composite, and the V / S×10 9 The half width W2 of the signal of the fluorine atoms contained in the second mixture prepared so that the value of reaches 35 nm measured by fluorine-19 nuclear magnetic resonance spectroscopy is W1 / W2≥1.

1.

5. A sheet comprising the composite according to claim 1 or 2. An electrochemical device comprising the composite according to claim 1 or 2. 7 . An electric storage device comprising a positive electrode layer, a negative electrode layer, and a separator separating the positive electrode layer from the negative electrode layer, comprising the composite according to claim 1 or 2 .

8. The power storage device according to claim 7, wherein At least one of the positive electrode layer, the negative electrode layer, and the separator includes the composite.

9. The power storage device according to claim 7, wherein At least one of the positive electrode layer and the negative electrode layer includes a current collecting layer, A protective layer in contact with at least one of the separator and the current collecting layer is provided. The protective layer includes the composite.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery, battery pack and vehicle

    JP2018045965A